2012
DOI: 10.4236/jdm.2012.22036
|View full text |Cite
|
Sign up to set email alerts
|

The development and validation of a risk score for predicting microalbuminuria in type 2 diabetic patients

Abstract: Objective: To develop and validate a prognostic scoring scheme for the prediction of microalbuminuria in type 2 diabetic patients of Thai descent. Methods: The clinical information from type 2 diabetic patients who were treated at community hospitals was used to develop a prediction model (derivation set). The model evaluated at a tertiary hospital (validation set). A stepwise logistic regression model was used to identify the independent risk variables from the derivation set and a simple point scoring system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Eghan et al [25] in a cross-sectional study including diabetes subjects found that BUN, among other variables, was a predictor of microalbuminuria. Zakerdish et al found in a study that albuminuria in diabetes subjects is correlated with BUN level, HbA1c, and duration of diabetes mellitus; however, no model was proposed to calculate the probability of subjects developing microalbuminuria [26] Two other models proposed by Scheven et al [18] and by Mongkolsomlit et al [16] did not consider the inclusion of BUN measures in the development of their corresponding models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eghan et al [25] in a cross-sectional study including diabetes subjects found that BUN, among other variables, was a predictor of microalbuminuria. Zakerdish et al found in a study that albuminuria in diabetes subjects is correlated with BUN level, HbA1c, and duration of diabetes mellitus; however, no model was proposed to calculate the probability of subjects developing microalbuminuria [26] Two other models proposed by Scheven et al [18] and by Mongkolsomlit et al [16] did not consider the inclusion of BUN measures in the development of their corresponding models.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the findings generally agree with those of previous studies. A study conducted in 2012 by Mongkolsomlit et al [16] included diabetic subjects in one Thai hospital. The researchers collected patient variables (e.g., age, gender, body mass index, glycemic control, blood pressure, dyslipidemia) through a case-control study design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the literature, we entered potential confounding variables into the multivariable model using an epidemiological approach. 29 Additionally, we evaluated collinearity between the variables before entering them into the multivariable model.…”
Section: Discussionmentioning
confidence: 99%